2001
DOI: 10.1145/503271.503216
|View full text |Cite
|
Sign up to set email alerts
|

Deadlock detection in distribution object systems

Abstract: The behaviour of a distributed system is largely determined by the use of synchronization primitives and threading policies of the underlying middleware. The inherent parallel nature of distributed systems may cause liveness problems, such as deadlocks and livelocks. An increasing number of distributed systems is built using object middleware. We exploit the fact that modern object middleware offers only a few built-in synchronization and threading primitives by suggesting UML stereotypes to represent each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…However, the proposed algorithm requires significantly fewer amount of structural analyses than TLBO method. When examining Table in terms of statistical results, it is observed that the values of the average weight, standard deviation, and worst weight obtained by the proposed algorithm are smaller than PSO, BB‐BC, RO, EHS, SAHS, TLBO, and ECBO methods listed in the table. In this table, we can see that a worst weight of 380.29 lb is achieved using BBO‐DE algorithm, which is less than that obtained by EHS, SAHS, and TLBO methods.…”
Section: Numerical Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the proposed algorithm requires significantly fewer amount of structural analyses than TLBO method. When examining Table in terms of statistical results, it is observed that the values of the average weight, standard deviation, and worst weight obtained by the proposed algorithm are smaller than PSO, BB‐BC, RO, EHS, SAHS, TLBO, and ECBO methods listed in the table. In this table, we can see that a worst weight of 380.29 lb is achieved using BBO‐DE algorithm, which is less than that obtained by EHS, SAHS, and TLBO methods.…”
Section: Numerical Testsmentioning
confidence: 99%
“…The comparison results of BBO‐DE with existing metaheuristic methods including PSO, BB‐BC, Ray Optimization (RO), EHS, SAHS, TLBO, CBO, and ECBO are presented in Table . It can be seen that the best result obtained by BBO‐DE is the same as that by TLBO but better than those of all other methods.…”
Section: Numerical Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, metaheuristic optimization algorithms are utilized in conjunction with an NN model to minimize the total cost of SMRFs in the framework of PBD. Gholizadeh and Milany [18] compared the performance of particle swarm optimization (PSO), [19] dolphin echolocation optimization (DEO), [20] enhanced colliding bodies optimization (ECBO), [21] and ECBO-II [18] in PBD optimization of SMRFs considering the initial cost. Their study demonstrated superiority of ECBO-II metaheuristic over the other algorithms.…”
Section: Introductionmentioning
confidence: 99%